Analisis karakteristik dan tingkat kekumuhan pada kawasan permukiman di Desa Pengambengan, Kabupaten Jembrana, Bali - Ni Luh Jaya Anggreni; I Gusti Ngurah Putu Dharmayasa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Rapid population growth leads to the expansion of residential areas, increasing the demand for land. Unpreparedness in anticipating the speed and dynamics of urban growth can result in the emergence of slum settlements. This study focuses on the settlements in Pengambengan Village, Jembrana Regency, Bali, which are predominantly inhabited by fishermen and are considered to be slums. If the growth of these slum settlements is not controlled, the environmental quality will continue to decline as these settlements expand. Therefore, it is crucial to understand the characteristics of these settlements. To understand the characteristics of these slum settlements, it is crucial to examine their features. Through this research, an analysis will be conducted to determine the characteristics of the slum settlement in Pengambengan. This study employed a mixed-method approach, combining data collection through observation and interviews, as well as data collection from various sources to complement existing survey results. The collected data was then analyzed and assessed based on the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 14/PRT/M/2018. The results of the analysis, which align with the 7 slum conditions including building structures, roads, water supply, drainage system, wastewater management, waste management, and fire protection, yielded a total score of 18. This indicates that the residential in Pengambengan is at a mild level of slum conditions. Despite being relatively low in slum severity, two important aspects should be noted-the provision of qualified drinking water and awareness of fire hazards, as these could have severe consequences for the residents of Pengambengan.